Managing for sales results : - Marks, Ron (John Wiley & Sons, 2008)
This book looks at various methods for recruiting salespeople, from the traditional to the radical, and shows you how to make the smartest, most profitable hiring decisions for your team. It argues that sales managers should put more emphases on coaching and recruiting, making it a priority for your sales organization. With the right recruiting and training strategies, you can find a constant stream of qualified candidates and beat your competitors to the best sales prospects.